2007
DOI: 10.1139/y07-084
|View full text |Cite
|
Sign up to set email alerts
|

XP-828L (Dermylex), a new whey protein extract with potential benefit for mild to moderate psoriasisThis article is one of a selection of papers published in this special issue (part 1 of 2) on the Safety and Efficacy of Natural Health Products.

Abstract: Natural health products (NHPs) or complementary and alternative medicine (CAM) are commonly used to prevent disorders or support the usual treatments of many diseases. XP-828L, a whey protein extract, has demonstrated potential benefits for the treatment of mild to moderate psoriasis. The aim of this study was to analyze further clinical data that demonstrated the clinical benefits and safety of the XP-828L in patients with psoriasis and the potential mechanism of action of this product in vitro. Oral administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Notably, for the same diseases, both turnip and whey had comparable proximity scores to the corresponding drugs. The proximal distance in the whey-psoriasis pair was Z c = −1.85; it has been reported that XP-828L, a protein extract isolated from bovine sweet whey, has potential benefit for mild to moderate psoriasis (Drouin et al, 2007 ). Whey was also proximal to prostate cancer (Z c = −1.66) and has been shown to increase the synthesis of glutathione (GSH), which may play an important role in preventing prostate cancer development through its antioxidant activities (Kent et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, for the same diseases, both turnip and whey had comparable proximity scores to the corresponding drugs. The proximal distance in the whey-psoriasis pair was Z c = −1.85; it has been reported that XP-828L, a protein extract isolated from bovine sweet whey, has potential benefit for mild to moderate psoriasis (Drouin et al, 2007 ). Whey was also proximal to prostate cancer (Z c = −1.66) and has been shown to increase the synthesis of glutathione (GSH), which may play an important role in preventing prostate cancer development through its antioxidant activities (Kent et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%